Письма Ивара Иваска Б. Л. Пастернаку [Letters of Ivar Ivask to Boris Pasternak] - Sakova, Aija (Slavica Revalensia, 2020)
This is a prefaced publication of three drafts of the letters that an American critic, a university professor, and a multilingual poet Ivar Ivask sent to the author of  “Doctor Zhivago” during the last year of Pasternak’s life (1959—1960). While Pasternak’s answers to Ivask were first published half a century ago in the addressee’s translation into English, the letters of Ivask, who initiated the correspondence, are published for the first time. All three letters are reproduced both in the original German, and in the Russian translation by Fedor Poljakov.